Role of biochar in biodegradation of nonylphenol in sediment: Increasing microbial activity versus decreasing bioavailability - Guanghuan Cheng (Nature Portfolio, 2017)
Abstract The observed strong sorption of hydrophobic organic contaminants (HOCs) to biochar presents potential implications for HOCs bioavailability and bioaccessibility in sediments, while biochar could impact sediment microbial ecology. However, the comprehensive study on the effects of biochar on HOC biodegradation coupled with bioavailability and microbial ecology are rarely documented. In this paper, the effects of biochar on the biodegradation of nonylphenol (NP) were investigated using 3 different NP concentrations (20, 50 and 500 mg/Kg) in sediments amended with different percentage of rice straw biochar (RC). Results showed that the influence of RC on NP biodegradation varied with different NP concentrations. At low NP concentrations, RC suppressed NP biodegradation by reducing NP bioavailability, while at high NP concentrations, moderate RC addition promoted biodegradation by reducing toxicity of NP to microbes. The effects of NP on microbial community structures were significant (P < 0.01), but those of RC were not significant (P > 0.05). The RC affected microorganisms through altering NP toxicity, microbial quantity and activity, but not microbial community structures. This study indicated that there could be an optimal biochar percentage in biochar-sediment systems at different HOC concentrations, which strengthened HOC biodegradation process and accelerated biodegradation rate, forming adsorption-biodegradation coupled bioremediation.